2006
DOI: 10.1159/000092892
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sleep Condition and Sleep-Related Psychological Activity after Cognitive-Behavior and Pharmacological Therapy for Chronic Insomnia

Abstract: Background: Previous studies of insomnia focused mainly on the improvement of sleep condition and ignored the effects of sleep-related psychological activity and daytime function after pharmacological and behavioral treatments. We compared the clinical effects of both therapies on sleep condition, sleep-related psychological activity and daytime function in chronic insomnia. Methods: Seventy-one patients with chronic insomnia were randomly divided into 4 groups and either received cognitive-behavior therapy (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 55 publications
1
73
0
2
Order By: Relevance
“…Findings from such studies generally suggest that combined approaches are slightly more effective than medication alone, but they produce similar benefits when compared to CBT alone. [1][2][3][4][5][6] The literature on long-term outcomes of combined therapies is even more limited, with only two studies having reported follow-up data extending to intervals of 12 months or longer after treatment. One study included 63 adults who were randomized to a six-week treatment involving CBT, zolpidem, combined CBT and zolpidem, or placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from such studies generally suggest that combined approaches are slightly more effective than medication alone, but they produce similar benefits when compared to CBT alone. [1][2][3][4][5][6] The literature on long-term outcomes of combined therapies is even more limited, with only two studies having reported follow-up data extending to intervals of 12 months or longer after treatment. One study included 63 adults who were randomized to a six-week treatment involving CBT, zolpidem, combined CBT and zolpidem, or placebo.…”
Section: Introductionmentioning
confidence: 99%
“…[110][111][112] These studies provide a limited assessment of temazepam in that they included small sample sizes of 19, 20, and 34 subjects, respectively. The overall quality of evidence from these studies is moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses for temazepam 15 mg were conducted for SL, TST and sleep quality. Two studies 110,112 were included in the meta-analysis of SL. These showed a reduction in subjective SL which exceeded the threshold for clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of bias was predominantly moderate. 89 Evidence from one small trial was insufficient to draw conclusions regarding the efficacy of multicomponent behavioral interventions in treating insomnia disorder in the general adult population.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…89,97 One was conducted in Australia 89 and one in Scotland. 97 Studies differed in how the stimulus control was delivered.…”
Section: Overview Of Studiesmentioning
confidence: 99%